2021
DOI: 10.3991/ijet.v16i02.17327
|View full text |Cite
|
Sign up to set email alerts
|

University Support, Teaching Competencies and Entrepreneurial Competencies in Software Engineering and Graphic Design Students

Abstract: The objective of this research was to evaluate how university support and teaching entrepreneurial competencies affect students' entrepreneurial com-petencies. As an empirical test, a sample of 201 software engineering and graphic design students from a university in Northwest Mexico was taken, where it was possible to corroborate three hypotheses. The results suggest that entrepreneurial competencies are influenced by external aspects, where the university can be understood as an open system, but also, as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreno, O. A. M and Marco Alberto Nuez Ramírez used software engineering and graphic design students in a Mexican university as a sample and found that the innovative ability of the students in this program was influenced to a certain extent by the triple-helix structural system of the university and that the student's professional competence and practical competence work together to promote students' innovation ability [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreno, O. A. M and Marco Alberto Nuez Ramírez used software engineering and graphic design students in a Mexican university as a sample and found that the innovative ability of the students in this program was influenced to a certain extent by the triple-helix structural system of the university and that the student's professional competence and practical competence work together to promote students' innovation ability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Jie Wen. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12] …”
mentioning
confidence: 99%
“…Teaching information resource database, as an important part of distance education in schools, includes multimedia material database, teaching plan database, courseware database, test question database, subject database, etc. [1][2][3][4][5][6]. At the same time, the resource database should also provide teachers and students with full-text retrieval, attribute retrieval, increase, decrease and classification of resources, and also provide functions such as compression, packaging and downloading [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%